Is Absence of Hydronephrosis a Risk Factor for Bleeding in Conventional Percutaneous Nephrolithotomy? - Kim, Hee Youn; Choe, Hyun-Sop; Lee, Dong Sup; Yoo, Je Mo; Lee, Seung-Ju (Urology Journal, 2020)
Purpose: There is conflict of evidence regarding whether absence of hydronephrosis is a risk factor for bleeding in percutaneous nephrolithotomy (PNL). Moreover, among the stone complexity scoring system used for PNL (Guy’s stone score, the S.T.O.N.E. nephrometry and the CROES nomogram), only the S.T.O.N.E. nephrometry score incorporates hydronephrosis as a risk factor. Therefore, this study aimed to compare perioperative outcomes according to the presence or absence of hydronephrosis in percutaneous nephrolithotomy (PCNL) patients and to investigate whether absence of hydronephrosis is a risk factor for blood transfusion rate. Materials and Methods: 281 patients who had undergone PCNL between December 2009 and April 2017 were divided according to the absence or presence of hydronephrosis (group I and group II, respectively). Perioperative outcomes were compared between the two groups. A multivariable regression analysis was performed to investigate whether hydronephrosis was a risk factor for blood transfusion rate. Results: Patients without hydronephrosis showed significantly longer operation time and admission period, lower stone-free rate and higher blood transfusion rate compared to patients with hydronephrosis (p < 0.05, p = 0.002, p = 0.011, and p < 0.05, respectively). Multivariate logistic regression analysis showed that hydronephrosis was a significant risk factor for blood transfusion (OR, 95% CI and p value was 0.353, 0.163-0.761 and 0.008, respectively). Conclusion: Based on the results of the current study, we found that absence of hydronephrosis was a significant risk factor for blood transfusion in conventional PCNL.